Comprehensive Electrocardiographic Analysis of Lead Exposed Workers: An Arrhythmic Risk Assessment Study. Issue 2 (10th June 2016) - Karakulak, Ugur N.; Yilmaz, Omer H.; Tutkun, Engin; Gunduzoz, Meside; Ercan Onay, Emine
Abstract : Background: To evaluate electrocardiographic parameters which are related with atrial and ventricular arrhythmias measured from 12‐lead surface electrocardiogram (ECG) in workers occupationally exposed to lead. Methods: Sixty lead‐exposed workers and 60 healthy controls were enrolled. Twelve‐lead surface ECG was recorded and measurements of P wave durations (Pmax, Pmin) and P wave dispersion (PWD), QT durations and dispersion (QTd), corrected QT (QTc), Tp‐e interval, and Tp‐e/QT ratio were analyzed. Results: The lead‐exposed and control groups were similar with respect to baseline demographic, laboratory, and transthoracic echocardiographic indices. PWD (26.3 ± 9.7 vs 22.0 ± 9.0 ms, P = 0.014), Pmin (89.9 ± 13.8 vs 79.2 ± 10.1 ms, P < 0.001), and Pmax (116.2 ± 15.0 vs 101.2 ± 14.2 ms, P < 0.001), QT maximum (377.0 ± 27.6 vs 364.9 ± 28.5 ms, P = 0.02), QTd (38.4 ± 16.5 vs 30.5 ± 12.4 ms, P = 0.004), Tp‐e interval (78.9 ± 16.5 vs 70.3 ± 14.5 ms, P = 0.003), and Tp‐e/QT ratio (0.22 ± 0.04 vs 0.20 ± 0.04, P = 0.013) were significantly higher in lead‐exposed workers. QT minimum and QTc values did not differ significantly. QT maximum, QTd, and Tp‐e/QT ratio were correlated with urine lead level and Tp‐e interval was correlated with both blood and urine lead levels. Conclusions: Lead‐exposed workers have a higher risk for atrial and ventricular arrhythmias even without overt cardiac diseases compared with healthy subjects. These workers should be followed closely for adverse cardiovascular outcomes especially arrhythmias.